Relationship between socio-demographic conditions and knowledge about the pre-conception risk in women in childbearing age - Adriana del Carmen Cáceres Cabrera; Rubén Darío García Núñez; María Aurelia San Juan Bosch (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2017)
Foundation: decreasing infant and maternal mortality in one of priorities in Ecuador,   therefore controlling pre conception risk factors are of great importance. Objective: to determine the relationship between the socio-demographic conditions and the knowledge about the pre conception risks in women at childbearing age. Methods: descriptive, correlational study, conducted from January to June 2016, which included 50 women of childbearing age from Barrio Lourdes, Riobamba, Ecuador. A structured interview was applied, validated by experts, who measured socio-demographic conditions and knowledge in the following dimensions: adequate age to get pregnant, unfavorable obstetric history; intergenesic age, use of contraceptives, concept of pre-conception risk, ideal weight, chronic diseases and pregnancy, toxic habits and pregnancy. Fisher's statistical test and Chi square were used to determine the relationship between the variables with a significance level of p <0.05. Results: 52% of the women were between 25-34 years old, 82% are mestizas; 40% married; 50% reached the baccalaureate; 50% were housewives and 72% had a regular socioeconomic level. Unsatisfactory knowledge predominated (76%); the concept dimension of pre-conception risk and ethnicity (p = 0.03), marital status and occupation with the knowledge of the toxic habits dimension (p = 0.018) and economic level (p = 0.001) were correlated. In addition, there was a relationship between the ideal weight and age dimension (p = 0.019). Conclusions: ethnicity was the socioeconomic condition that most influenced the low knowledge about pre conception risk; marital status, occupation, economic level and age influenced knowledge about risk factors.